Injury in the transgender population: What the trauma surgeon needs to know. Issue 4 (October 2018) - Morrison, Shane D.; Kolnik, Sarah M.; Massie, Jonathan P.; Crowe, Christopher S.; Dugi, Daniel; Friedrich, Jeffrey B.; Pham, Tam N.; Berli, Jens U.; O'Keefe, Grant E.; Bulger, Eileen M.; Maier, Ronald V.; Mandell, Samuel P.
Abstract : ABSTRACT: Gender dysphoria, or the distress caused by the incongruence between a person's assigned and experienced gender, can lead to significant psychosocial sequelae and increased risk of suicide (>40% of this population) and assault (>60% of this population). With an estimated 25 million transgender individuals worldwide and increased access to care for the transgender population, trauma surgeons are more likely to care for patients who completed or are in the process of medical gender transition. As transgender health is rarely taught in medical education, knowledge of the unique health care needs and possible alterations in anatomy is critical to appropriately and optimally treat transgender trauma victims. Considerations of cross-gender hormones and alterations of the craniofacial, laryngeal, chest, and genital systems are offered in this review. Further research on the optimal treatment mechanisms for transgender patients is needed.